2004
DOI: 10.1117/12.545928
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence lifetime to image epidermal ionic concentrations

Abstract: Measurements of ionic concentrations in skin have traditionally been performed with an array of methods which either did not reveal detailed localization information, or only provided qualitative, not quantitative information. FLIM combines a number of advantages into a method ideally suited to visualize concentrations of ions such as H + in intact, unperturbed epidermis and stratum corneum (SC). Fluorescence lifetime is dye concentration-independent, the method requires only low light intensities and is there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…In different approaches to lifetime-analysis such species would be difficult to discern, but, when present, complicate mathematical fittings. Further, a shift of pH would only affect the SC-extracellular domain, as shown in our prior data [5, 6, 26]. Thus, we concluded that our measurements were suitable for rodent skin, and artifactual lifetime components were not present in our images.…”
Section: Resultssupporting
confidence: 67%
“…In different approaches to lifetime-analysis such species would be difficult to discern, but, when present, complicate mathematical fittings. Further, a shift of pH would only affect the SC-extracellular domain, as shown in our prior data [5, 6, 26]. Thus, we concluded that our measurements were suitable for rodent skin, and artifactual lifetime components were not present in our images.…”
Section: Resultssupporting
confidence: 67%